Factors that influence parents' choice of pre-schools education in Malaysia: an exploratory study - Dahari, Zainurin; Ya, Mohd Sabri (Centre for Promoting Ideas (CPI), USA., 2011)
The objective of this study is to identify the important factors contribute most to parents' choice of pre-school for their children. Parents' choice of pre-school is influenced by various factors that are mostly associated with the pre-school institution itself. Parent have different educational believes and preferences which puts them in a dilemma when making decision for their children pre-school education. it is important for pre-school businesses to meet the needs of both parents and children in order to attract and retain their customer. Data was collected using a survey questionnaire. The sample consisted of 162 parents who have pre-school children. Multiple regression analysis was used to identify the predictor variables that contributed to the choice of pre-schools. The main factors that influence parents' choice of pre-schools are branding, private-run institutions, safety and security, quality of teaching and hygiene. English medium and religion-based pre-schools are the preferred pre-schools chosen by these parents.